Research on the Impact of Psychological Capital on the Employment Quality of College Students - Zhao, Peng (Journal of Educational Research and Policies, 2025)
The employment of college students, as a key social issue and persistent challenge in contemporary society, is closely related to the solution path and the quality of higher education. Psychological capital, as an important concept in positive psychology, is of great significance in improving the employment quality of college students. Starting from the current employment situation of college students, this article analyzes and summarizes the factors that influence the quality of employment through psychological capital, and ultimately proposes suggestions and strategies to improve the quality of employment by enhancing the psychological capital of college students.